The Influence of Cooperatives and Trade Unions on Employee Welfare at PT Adis Dimension Footwear Tangerang Regency - Kismiati, Evi; Setiawan, Temmy (Faculty of Science and Technology University of Pramita Indonesia, 2025)
Employee welfare is a crucial factor in maintaining worker productivity and loyalty within an organization. This research is motivated by the important role of Cooperatives and Trade Unions in efforts to improve employee welfare at PT Adis Dimension Footwear, Tangerang Regency. Issues such as the cooperative's less responsive service and complicated loan procedures, as well as the assumption that union leaders still side with management and are less responsive to employee complaints, are suspected to have an impact on the decline in employee welfare. To test this suspicion, this study uses a quantitative approach with a causal associative method, which aims to determine the influence or relationship between two or more variables. Data were collected by distributing questionnaires to 82 employee respondents of PT Adis Dimension Footwear. Data analysis was carried out using multiple linear regression analysis with the help of SPSS software version 25.0. The results of the regression analysis show that the Cooperative variable has a regression coefficient (B) of -0.578 with a significance value (Sig.) of 0.000, indicating a significant negative influence. Meanwhile, the Workers Union variable has a regression coefficient (B) of 0.968 with a Sig. 0.000, indicating a significant and strong positive influence on Employee Welfare. Simultaneously, an F-test (ANOVA) obtained an F-value of 212.372 with a significance value of 0.000, indicating that cooperatives and labor unions jointly have a significant influence on Employee Welfare. The coefficient of determination (R2) indicates that 84.2% of the variation in Employee Welfare can be explained by cooperatives and labor unions, while the remaining 15.8% is explained by other factors outside the model.